Fresno County Women Lawyers/Fresno County Bar Association Seminar on Judicial Selection Held at Ramada Inn - Watkins, Howard::::::::: (1989)
Appointments Secretary Terrence Flanagan speaking with Judge Judith Chirlin looking on